2016
DOI: 10.1111/bjh.14282
|View full text |Cite
|
Sign up to set email alerts
|

Sole rearrangement but not amplification of MYC is associated with a poor prognosis in patients with diffuse large B cell lymphoma and B cell lymphoma unclassifiable

Abstract: Rearrangement of MYC is associated with a poor prognosis in patients with diffuse large B cell lymphoma (DLBCL) and B cell lymphoma unclassifiable (BCLU), particularly in the setting of double hit lymphoma (DHL). Yet, little is known about outcomes of patients who demonstrate MYC rearrangement without evidence of BCL2 or BCL6 rearrangement (single hit) or amplification (>4 copies) of MYC. We identified 87 patients with single hit lymphoma (SHL), 22 patients with MYC-amplified lymphoma (MYC amp) as well as 127 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 33 publications
2
41
2
1
Order By: Relevance
“…DH had no additional prognostic effect compared to SH in this study. This is in accordance with other previously published studies which could not demonstrate an additional prognostic effect of DH compared with SH in large cohorts of patients with DLBCL and MYC translocation 2,3,6. A recent study of patient samples from a large randomized trial of LBCL also found a prognostic effect of both SH and DH 4.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…DH had no additional prognostic effect compared to SH in this study. This is in accordance with other previously published studies which could not demonstrate an additional prognostic effect of DH compared with SH in large cohorts of patients with DLBCL and MYC translocation 2,3,6. A recent study of patient samples from a large randomized trial of LBCL also found a prognostic effect of both SH and DH 4.…”
supporting
confidence: 93%
“…According to WHO, the prognostic importance of MYC translocation in LBCL is however still not sufficiently clarified. So‐called single hit MYC translocation (SH) without concurrent BCL2 and/or BCL6 rearrangements has also been associated with inferior survival, and in addition, we and others described particularly poor outcome both in patients with MYC‐SH or DH with an immunoglobulin‐( IG ) MYC translocation partner gene . In addition, stratification of patients with MYC ‐SH and DH translocations according to MYC protein expression level and/or BCL2 expression level has been suggested to impact patient survival in few studies.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently observed derangement leading to MYC protein overexpression involves the translocation of MYC to the immunoglobulin gene (IG) locus. [22][23][24][25][26] The MYC-IG rearrangement is the hallmark of BL and serves as a defining characteristic in approximately 60% of HGBL cases and in a minority of cases of DLBCL.…”
Section: Mycmentioning
confidence: 99%
“…Although double-hit or triple-hit B-cell lymphomas are well-known with worse prognosis, previous studies concerning the prognostic impact of a c-MYC rearrangement alone have been controversial. Some studies demonstrated that a c-MYC rearrangement leads to poor prognosis even without BCL2 or BCL6 rearrangements [22,23], while a c-MYC rearrangement alone did not show significant prognostic impact in other studies [24,25]. The rearrangement of BCL2, BCL6, or PAX5 alone has not been associated with worse outcome in DLBCL patients [26,27], while the prognostic impact of CCND1 rearrangement in DLBCL has been controversial [28].…”
Section: Discussionmentioning
confidence: 99%